2013
DOI: 10.1530/rep-13-0114
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression of granulosa cells after ovarian superstimulation in beef cattle

Abstract: Microarray analysis was used to compare the gene expression of granulosa cells from dominant follicles with that of those after superstimulatory treatment. Cows were allocated randomly to two groups (superstimulation and control, nZ6/group). A new follicular wave was induced by ablation of follicles R5 mm in diameter, and a progesterone-releasing device controlled internal drug release (CIDR) was placed in the vagina. The superstimulation group was given eight doses of 25 mg FSH at 12-h intervals starting from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 74 publications
1
31
0
Order By: Relevance
“…To determine if and to what extend superstimulation affect follicles and oocytes, microarray technology was used to compare granulosa cell gene expression in superstimulated follicles versus dominant follicles from a natural cycle (Dias et al, 2013c). The superstimulation protocol used in this study included exogenous administration of FSH over 4 days after follicular wave synchronization and LH 24 h after progesterone-device removal.…”
Section: Single Dominant Follicle Versus Many Follicles After Fsh Stimentioning
confidence: 99%
“…To determine if and to what extend superstimulation affect follicles and oocytes, microarray technology was used to compare granulosa cell gene expression in superstimulated follicles versus dominant follicles from a natural cycle (Dias et al, 2013c). The superstimulation protocol used in this study included exogenous administration of FSH over 4 days after follicular wave synchronization and LH 24 h after progesterone-device removal.…”
Section: Single Dominant Follicle Versus Many Follicles After Fsh Stimentioning
confidence: 99%
“…By providing continuous exogenous FSH support, regression of subordinate follicles can be prevented so that they assume qualities of a dominant follicle. Recently, a molecular study of granulosa cells indicated that gene expression in follicles undergoing superstimulation was altered compared to a single, naturally occurring dominant follicle [27]. Twenty-four hours after LH administration, genes related to growth and oxidative stress response were upregulated in granulosa cells of follicles undergoing a 4-day FSH superstimulation protocol as compared to the single dominant follicle of an unstimulated follicular wave.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the evaluation of the expression of LHR messenger RNA in granulosa cells of superstimulated and single, naturally occurring dominant follicles 12 hours after progesterone device removal revealed that expression of LHR was decreased in superstimulated follicles [29]. As a result, follicles following the conventional 4-day FSH superstimulation protocol appeared to be less mature and less responsive to LH when compared to a naturally occurring, single dominant follicle [27]. In this regard, studies evaluating the expression of these genes in granulosa cells of follicles undergoing extended FSH support (analogous to present study) may provide valuable insight into the mechanisms underlying the observed improvement in superovulatory response [19,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Adam et al (2012) furthermore indicated that the EGFR is one of the growth factor receptors directly targeted by DCN in human GCs and DCN is a local regulator of folliculogenesis, ovulation and the functional lifespan of the CL in primates. Recent studies demonstrated that the expression of FN was elevated in the superstimulation group and its expression was reported to be inversely related to follicle maturation (Berkholtz et al, 2006;Dias et al, 2013;Yasuda et al, 2005). TIMP3 was first discovered as an ECM bound protein and participated in changing the ECM (Li and Curry, 2009).…”
mentioning
confidence: 99%